Pencarian Lowongan Pekerjaan Berbasis Agen Berdasarkan Profil Pencari Kerja dengan Pendekatan Semantic Web Service - Teguh Susyanto; Khabib Mustofa (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2016)
Currently, job searching service still has many weaknesses and often fails to provide relevant job information that matches the needs of job seekers. This is due to the searching method applied in the search engines still uses the syntax-based matching and the lack of integration among the job service providers. Therefore it’s difficult for the job seekers to get the desired information. To overcome these weaknesses, a prototype of a job vacancy searching by involving a web service as a job information provider is proposed.This thesis is aimed to create job search based on the personalization of job seeker by combining multi agent and semantic web service approaches.The designing of the prototype used a multiagent technology whose capability was to call job service provider and run matching process of the job vacancy appropriate with the job seeker’s profile automatically. Algorithm of the service selection used service matching and Simple Additive Weighting. The similary between the job offer and the job seeker’s profile was calculated by using semantic algorithm. Based on the testing carried out to the respondents, it’s stated that this prototype has been able to give recommendation of job appropriate with the job seeker’s.